CAUSES AND OUTCOME OF CHILDREN WITH LOWER GASTROINTESTINAL BLEEDING (LGIB) PRESENTING AT TERTIARY CARE HOSPITAL - Dr Misbah Ullah Khan; Dr Ruba Gul; Dr Sadiq Akbar; Dr Noor Ul Haram Khattak; Dr Tanzeela; Dr Zia Muhammad (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Lower gastrointestinal bleeding (LGIB) in children is a concerning clinical presentation with a diverse range of underlying causes. Prompt diagnosis is essential to guide effective management and improve outcomes. Objective: To identify the causes and assess the clinical outcomes of children presenting with LGIB at a tertiary care hospital in Pakistan. Materials and Method: This was a descriptive cross-sectional study carried out at Khyber Teaching Hospital Peshawar, Pakistan in the duration from February 2024 and July 2024. The study involved the assessment of 300 pediatric patients with LGIB that was conducted with the help of clinical examination and colonoscopy, imaging studies, and histopathology. Findings: The most frequent cause was juvenile polyps (32%), followed by non-specific colitis (20.7), SRUS (10.3), and IBD (10 percent). The diagnostic yield of colonoscopy was high (93.3%), and the majority of the patients responded favorably either to conservative or endoscopic therapy. In 10 percent of the cases, surgery was expected. Conclusion: Early colonoscopic evaluation is crucial for timely diagnosis and management of pediatric LGIB.